Effectiveness of Ginger Drink (Zingiber Officinale Var Rubrum) on Reducing Nausea and Vomiting in Trimester I Pregnant Women - Ika Wahyuni; Ita Herawati; Aninda Dinar Widiantari; Farida Murtiani (Indonesian Journal of Global Health Research, 2024)
Nausea and Vomiting of Pregnancy (NVP) can become hyperemesis gravidarum thereby increasing the risk of pregnancy disorders. Ginger is an herbal plant that has long been known to prevent nausea and vomiting. The Aim study to determine the effectiveness of giving ginger drink (zingiber officinale var rubrum) to reduce nausea and vomiting in first trimester pregnant women. Quasi Experiment Research with the design used is One Group Pretest-Post Test Design. The sample in this study was the first trimester pregnant women at the Pratama Clinic Yardi Prima Tambun Bekasi as many as 33 mothers who were taken by purposive sampling. The intervention was carried out by giving 2.5 grams of white ginger sliced and brewed with 250 ml of warm water plus 10 grams of sugar (1 tablespoon) taken 2x1 a day for 4 days. Data were obtained by observing and measuring Nausea and Vomiting using the PUQE-24 instrument. Data analysis was univariate and bivariate with dependent T-test. The average Puqe-24 score before the ginger intervention was 9.79 and most of them were in the category of moderate nausea and vomiting as many as 23 (69.7%). The average emesis score after giving ginger was 6.64 and most of them were in the category of mild 14 (42.4%) and 2 (6.1%) not nausea and vomiting. There is an effect of giving ginger (zingiber officinale var rubrum) to mothers with NVP with P value (0.000) <α (0.05). Ginger is effective in reducing emesis gravidarum.